Scientific Committee Member - Antoniou, Maria G. (My University, 2026)
Scientific Committee Member of the IWA Regional Conference on Waste and Wastewater Management, Science and Technology (WWMST 2013), 26-28 June 2013, Limassol, Cyprus.